HAKEKAT TAFSIR SURAT AL-FATIHAH (Pemahaman Hakikat Ibadah Kepada Allah Swt Dalam Menghadapi Persoalan Kehidupan) - Andy, Safri (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2019)
Surah al-Fatihah is a special letter of 114 letters in the Qur'an. This privilege has placed it as a letter that was recited in a number of times and became part of the pillars of prayer. In the sunglasses of tasawauf, al-Fatihah which is believed by one verse, namely Iyyaka Na`budu wa Iyyaka Nasta`in is the key in the straightness of a servant's faith to only Allah SWT, and plead with Him. The application in Sufism is the closeness of a servant to Allah who is intimately intertwined, thus creating a deep sense of love. The love of a servant to Allah SWT, has placed himself in the ability of himself to answer various problems and solve problems in his life. The above study is a study that is rarely achieved and owned by the servants of Allah, so that the Fatihah does not color his life in facing problems and problems. Therefore, discussing the nature of surat al-Fatihah as a key in creating a servant's closeness in worshiping Allah Almighty to be able to face life's problems and be able to realize happiness in the world and in the hereafter. Happiness is achieved by requiring our Islamic through intact in worshiping God Almighty, as God